β-Phase poly(vinylidene fluoride) films encouraged more homogeneous cell distribution and more significant deposition of fibronectin towards the cell–material interface compared to α-phase poly(vinylidene fluoride) films - Low, Yuen Kei Adarina (2014)
The piezoelectric response from β-phase poly (vinylidene fluoride) (PVDF) can potentially be exploited for biomedical application. We hypothesized that α and β-phase PVDF exert direct but different influence on cellular behavior. α- and β-phase PVDF films were synthesized through solution casting and characterized with FT-IR, XRD, AFM and PFM to ensure successful fabrication of α and β-phase PVDF films. Cellular evaluation with L929 mouse fibroblasts over one-week was conducted with AlamarBlue® metabolic assay and PicoGreen® proliferation assay. Immunostaining of fibronectin investigated the extent and distribution of extracellular matrix deposition. Image saliency analysis quantified differences in cellular distribution on the PVDF films. Our results showed that β-phase PVDF films with the largest area expressing piezoelectric effect elicited highest cell metabolic activity at day 3 of culture. Increased fibronectin adsorption towards the cell-material interface was shown on β-phase PVDF films. Image saliency analysis showed that fibroblasts on β-phase PVDF films were more homogeneously distributed than on α-phase PVDF films. Taken collectively, the different molecular packing of α and β-phase PVDF resulted in differing physical properties of films, which in turn induced differences in cellular behaviors. Further analysis of how α and β-phase PVDF may evoke specific cellular behavior to suit particular application will be intriguing.